A Near-Infrared Range Photodetector Based on Indium Nitride Nanocrystals Obtained Through Laser Ablation - (:unkn) unknown (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2014)
We present a proof-of-concept photodetector that is sensitive in the near-infrared (NIR) range based on InN nanocrystals. Indium nitride nanocrystals (InN-NCs) are obtained through laser ablation of a high pressure chemical vapor deposition grown indium nitride thin film and are used as optically active absorption region. InN-NCs are sandwiched between thin insulating films to reduce the electrical leakage current. Under -1 V applied bias, the recorded photoresponsivity values within 600-1100-nm wavelength range are as high as 3.05 x 10(-2) mA/W. An ultrathin layer of nanocrystalline InN thin film is, therefore, a promising candidate for NIR detection in large area schemes.
Keywords: Photodetector; near-infrared (NIR); indium nitride; nanocrystals; INN; NANOWIRES